Phoxocephalidae - Taylor, Joanne (Zootaxa, 2009)
Nine species from three genera of Phoxocephalidae (Crustacea: Amphipoda) are reported from the Great Barrier Reef, Queensland, Australia. Seven species are new to science including five species of Birubius Barnard & Drummond, 1976: Birubius banksi sp. nov., Birubius casuarina sp. nov., Birubius kingae sp. nov., Birubius oti sp. nov. and Birubius parvus sp. nov.; one species of Limnoporeia Fearn-Wannan, 1968: Limnoporeia cooki sp. nov. and one species of Metaphoxus Bonnier, 1896: Metaphoxus varanus sp. nov. Limnoporeia woorake Barnard & Drummond, 1978 is reported for the first time from the Great Barrier Reef and more records of Birubius batei (Haswell, 1879) are reported, prompting the designation of a neotype for the species. These records expand the number of phoxocephalid species previously recorded from the Great Barrier Reef.